2023
DOI: 10.3390/vaccines11051010
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Vaccination in the WHO African Region: Progress Made in 2022 and Factors Associated

Franck Mboussou,
Bridget Farham,
Sheillah Nsasiirwe
et al.

Abstract: This study summarizes progress made in rolling out COVID-19 vaccinations in the African region in 2022, and analyzes factors associated with vaccination coverage. Data on vaccine uptake reported to the World Health Organization (WHO) Regional Office for Africa by Member States between January 2021 and December 2022, as well as publicly available health and socio-economic data, were used. A negative binomial regression was performed to analyze factors associated with vaccination coverage in 2022. As of the end … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 29 publications
1
7
0
Order By: Relevance
“…Several reasons likely account for low coverage with COVID-19 vaccines, including limited political commitment, logistical challenges, low perceived risk of COVID-19 illness, and variation in vaccine confidence and demand ( 3 ). Country immunization program capacity varies widely across the African Region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several reasons likely account for low coverage with COVID-19 vaccines, including limited political commitment, logistical challenges, low perceived risk of COVID-19 illness, and variation in vaccine confidence and demand ( 3 ). Country immunization program capacity varies widely across the African Region.…”
Section: Discussionmentioning
confidence: 99%
“…To support the COVAX mission, increase population immunity, protect health systems, and facilitate economic recovery from the pandemic, WHO announced ambitious targets to administer a primary COVID-19 vaccination series to 10% of the total global population by the end of 2021 and 70% by mid-2022 ( 2 ). However, disparities in access to COVID-19 vaccines for low-income countries existed worldwide until the end of 2021, and a supply sufficient for effective rollout in the WHO African Region was therefore delayed until early 2022 ( 3 ). In July 2022, WHO recommended that all countries redirect efforts and focus on vaccinating priority populations, including health care workers, older adults (persons aged ≥50 years), and other high-risk groups (e.g., pregnant women, persons with comorbidities, and those with immunocompromising conditions) ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…In contrast to the Kenyan study, an analysis of COVID-19 vaccination in the WHO African region found that only 40.9% of HCWs had completed the primary vaccination series by the end of 2022 [ 11 ]. Women comprise approximately 60% of the HCWs at AKUH-N; therefore, it was not surprising that more women (56.5%) than men participated in our study.…”
Section: Discussionmentioning
confidence: 99%
“…The slow COVID-19 vaccination rates reported on the African continent may present a threat to global recovery from the endemic phase of the pandemic. 15 …”
Section: Introductionmentioning
confidence: 99%
“…In a paper published in 2021, we previously showed that to achieve a COVID-19 vaccination coverage of at least 60% by mid-2022—a target set by African heads of governments, the West African subregion must increase the speed of COVID-19 vaccinations by four times the rate as of 3 months after vaccine deployment. 16 Few studies 15 17 have reported COVID-19 vaccine coverage across all African countries. To our knowledge, no published study has reported the vaccination trajectory in the context of the speed needed to achieve the WHO target, or compared modelled or projected COVID-19 vaccination coverage rates with ‘actual’ or ‘observed’ coverage rates.…”
Section: Introductionmentioning
confidence: 99%